Narga the sea monster - Blade, Adam; Tucker, Ezra N. (Scholastic New York, 2010)
In the perilous Black Ocean lurks Narga the Sea Monster. As well as preying on the rebels and fighting evil wizard Malvel, Narga is holding one of the good Beasts of Avantia captive. Can Tom set the good Beast free, or will it remain trapped in the Dark Realm for ever?